The Impact of Agricultural Land Changes to Industrial Area in Sumberjaya District, Majalengka - Muhfidlatul Qiraati; Mohammad Abi Rafdi; Imelda Chaerani Sunarti (Jurnal Perencanaan Wilayah dan Kota, 2025)
Land experiences inevitable dynamics of change. Given the limited nature of land, as eras develop and the population increases, agricultural land can also experience changes in use. The construction of the Cipali Toll Road has contributed to the dynamics of land use in Majalengka Regency, especially in Sumberjaya District. The dynamics of development have triggered changes in the area of ​​agricultural land into industrial areas. The purpose of this study is to examine the impact of changes in agricultural land into industrial areas in Sumberjaya District, Majalengka Regency. This study uses a qualitative descriptive approach using in-depth interviews. The sampling technique used is purposive sampling. The analysis technique used is content analysis to identify, understand, describe, and obtain an overview of the impact of changing agricultural land into an industrial areas. The result is the change in the area of agricultural land into an industrial area in Sumberjaya District has caused various impacts. The agricultural land that experienced the greatest change was changing into industry with a percentage of 65.08 (from 2009 to 2022). The activity of changing the function of agricultural land into an industrial area has greatly affected various aspects of the surrounding community’s life, including changes in (1) the environment which has an impact on the quality of water polluted by waste, waste is increasing with the increasing population, and water shortages; (2) social issues, including rising crime rates;, and (3) economic issues, including changes in livelihoods, changes in people's income, and opening of new jobs